Meningkatnya Pekerja Anak (Studi Konsep Maslahah) - Wahyuni, Indar (Kopertais Wilayah X Jawa Tengah, 2017)
AbstractChildhood is a growth process both physical and psyche, then ideally the children should be protected from from various behaviors that interfere with the growth. Therefore, the childrenâs rights should be guaranteed such as getting health, education and play. Then, there are many factors causing the existence of child labor. And poverty case is mentioned as the main factor that led to the emergence of child labor. Moreover, the risk and the impact of childrenâs involvement in work, means everything that experienced and felt annoying up to harm their physical and psychological. Although the poverty is often used as a reason of the child labor, but all of it are seized the childâs rights. The child who works before their age will make weak next generation. It is not apropriate with maqasid asy-Syariâah concept, one of them keep the five things, including one of dharuriyyah need that keep the childâs psyche. It is strenghtened by the quotation from the Qurâan. The impact of child labor in both short time and long time, of course it is so damage their both physical and psychological as stated in Q.S. an-Nisaâ(4): 9. It becomes a base of why child labour is not allowed. It is as mental protection form which is a dharuriyyah need. Although the child labour can help the family economic for live, in other case child labour must be avoided considering the disadvantage is bigger than its advantage. Meanwhile, if it is in order to help parent and does not interfere both their mental and their physical then it is allowed.Â Keyword: Child, child labour, maslahah/goodness